Pengelolaan Pemanfaatan Nanas yang Ramah Lingkungan dengan Sistem Pengujian Pengendalian Kas - Ramdani, Chaeru Syahru; Nurhasan, Yunus; Sahara, Lia Ira; Septanta, Rananda (Jurnal PKM Manajemen Bisnis, 2025)
The lack of access to practical knowledge about environmentally sustainable resource utilization and basic financial management among underprivileged students highlights the need for educational outreach programs. In response, a community service activity was carried out at the Pondok Miri Orphanage Foundation in South Tangerang, targeting 50 students as participants. This initiative, organized by 10 lecturers from Pamulang University, aimed to improve the students’ understanding of eco-friendly pineapple processing and introduce them to a simple cash control testing system. The program was structured into three main stages: preparation, implementation, and reporting. The methods applied included interactive lectures, group discussions, and hands-on practice sessions. Through this approach, participants were trained to process pineapples into environmentally sustainable products while learning to track basic financial transactions related to production. The results showed increased participant engagement, improved knowledge, and practical skills in both sustainable processing and cash management. Feedback from the participants and the foundation was overwhelmingly positive, indicating the relevance and impact of the training. This community service not only delivered essential life skills but also contributed to the empowerment and self-reliance of orphaned and underprivileged youth.